Saccadic Adaptation Alters the Attentional Field - Wick, Farahnaz A.; Garaas, Tyler W.; Pomplun, Marc (Frontiers in Human Neuroscience, 2016)
It is currently unknown whether changes to the oculomotor system can induce changes to the distribution of spatial attention around a fixated target. Previous studies have used perceptual performance tasks to show that adaptation of saccadic eye movements affects dynamic properties of visual attention, in particular, attentional shifts to a cued location. In this study, we examined the effects of saccadic adaptation on the static distribution of visual attention around fixation (attentional field). We used the classic double step adaptation procedure and a flanker task to test for differences in the attentional field after forward and backward adaptation. RT measures revealed that the shape of the attentional field changed significantly after backward adaptation as shown through altered interference from distracters at different eccentricities but not after forward adaptation. This finding reveals that modification of saccadic amplitudes can affect metrics of not only dynamic properties of attention but also its static properties. A major implication is that the neural mechanisms underlying fundamental selection mechanisms and the oculomotor system can reweight each other.